Multi-mode absorption spectroscopy - Arita, Y; Ewart, P (2008)
A method of absorption spectroscopy is reported that uses a comb of laser modes that is frequency tuned over the mode spacing. Absorption of individual modes in a gaseous absorber is detected by reduction in the total transmitted power as the modes are tuned yielding a signature characteristic of the absorbing species. Analysis of the signal provides information on the species concentrations, temperature and pressure. The potential of the method for rapid detection of multiple transitions with high resolution and wide spectral range is demonstrated using a multi-mode diode laser to detect multiple transitions in the A-band b1 Σg+ - X3 Σg- of molecular oxygen around 760 nm. Application of the technique to gas-phase thermometry with a precision of ±2 % is reported. © 2007 Elsevier B.V. All rights reserved.